A critical analysis of the deductibility for income tax purposes of dual-purpose expenditure - Pickup, Richard Kenneth (Rhodes University, Faculty of Commerce, Department of Accounting, 2016)
This thesis critically analysed the apportionment of dual-purpose expenditure. In doing so, two categories of dual-expenditure were examined: expenditure that has been incurred for both trade and non-trade purposes, and expenditure that has been incurred to produce both taxable and exempt income. In conducting this analysis, this thesis set out to answer three questions: has the apportionment of dual-purpose expenditure been officially sanctioned in South Africa, when does the need for apportionment arise, and on what basis should a taxpayer apportion expenditure that has been incurred for a dual purpose? A doctrinal methodology was applied to the documentary data which consisted of relevant tax legislation; South African, Australian and English case law; and commentary of experts in the field of tax law. From the analysis performed, it was revealed that the apportionment of dual-purpose expenditure has been officially sanctioned in South Africa. In addition, it was concluded that the applicable legal principles for determining the need for apportionment and for performing the apportionment calculation are clear and well-established. The difficulty which taxpayers, the courts and the South African Revenue Service face, however, is applying these principles in practice. This research therefore concluded that there is a need for further guidance in this complex area of tax law. In addition, this research proposed some recommendations which could provide more certainty and clarity.
Keywords: Uncatalogued